Bridges or Barriers? Cross-boundary communication and governance mismatches in co-managed protected areas - Rebecca Borges; Roberta Sá Leitão Barboza; Theresa Schwenke (PLoS ONE, 2026)
Protected areas are often faced with mismatches that pose challenges to governance. Spatial mismatch is the geographical level of a conservation issue not matching the spatial level of the governance instruments for tackling this issue. It occurs in sustainable-use protected areas, for example, when local users only get involved in co-management of areas they inhabit, not of those they extract resources from. We examine the roles of key actors in transboundary communication between marine protected areas where this type of spatial mismatch was previously detected. Applying social network analysis we gauge communication networks in four Brazilian coastal-marine extractive reserves. Our results underline the importance of including qualitative data when considering network interventions for promoting integrated, cross-boundary co-management. Interviews revealed tensions between the federal, protected area Administration Agency and local users' associations. Despite high centrality, the Administration Agency is perceived as a barrier to management, while the NGO and Academia were perceived as bridges, shown through high eigenvector centralities and participants’ statements. Academia appeared as an undisputed bridging partner, while the NGO was viewed with skepticism. Tensions between the users’ associations, representing non-governmental actors, and the Administration Agency are caused by a lack of clarity and agreement on the roles of the government and local populations. They hinder co-management of the mangrove commons. Overall, there is a clear mismatch between the generally assigned protected area management council functioning and the actual communication and collaboration network in place. Further challenges for transboundary co-management in the study area include weak management councils, funding constraints, and digitalization issues, which point to mismatches other than just the spatial one previously identified. This paper highlights their impact on governance and collaboration within the extractive reserves. We propose the creation of a forum of councils to overcome these obstacles and enhance institutional collaboration. This would enhance cross-boundary communication and allow for management at a regional level that addresses transboundary challenges and alleviates various types of governance mismatches.